2012
DOI: 10.1089/ten.teb.2011.0737
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Based Strategies for Bone Tissue Engineering and Orthopedic Implants

Abstract: Bisphosphonates (BPs) are a group of well-established drugs that are applied in the development of metabolic bone disorder-related therapies. There is increasing interest also in the application of BPs in the context of bone tissue engineering, which is the topic of this review, in which an extensive overview of published studies on the development and applications of BPs-based strategies for bone regeneration is provided with special focus on the rationale for the use of different BPs in three-dimensional (3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 165 publications
2
59
0
1
Order By: Relevance
“…[59][60][61] The mechanism for this enhancement in osseointegration is believed to involve reduction in osteoclast activity and increase in osteoblast activity. 58 Since BPs can suppress fibroblast proliferation, as observed herein as well as in other studies, 19,21,22 BP-modified surfaces can potentially reduce fibrous encapsulation and provide another positive aspect for osseointegration. However, since we have used mouse cell lines as the model fibroblast and osteoblast system, we cannot rule out that the corresponding human cells may act differently.…”
Section: Coculture Of Fibroblasts and Osteoblastssupporting
confidence: 69%
See 1 more Smart Citation
“…[59][60][61] The mechanism for this enhancement in osseointegration is believed to involve reduction in osteoclast activity and increase in osteoblast activity. 58 Since BPs can suppress fibroblast proliferation, as observed herein as well as in other studies, 19,21,22 BP-modified surfaces can potentially reduce fibrous encapsulation and provide another positive aspect for osseointegration. However, since we have used mouse cell lines as the model fibroblast and osteoblast system, we cannot rule out that the corresponding human cells may act differently.…”
Section: Coculture Of Fibroblasts and Osteoblastssupporting
confidence: 69%
“…Recently, there have been many studies that focused on the application of BPs in bone tissue engineering and regeneration, as highlighted by the review article by Cattalini et al 58 Some in vivo studies have indicated that coating BPs on Ti implant surfaces can significantly improve osseointegration. [59][60][61] The mechanism for this enhancement in osseointegration is believed to involve reduction in osteoclast activity and increase in osteoblast activity.…”
Section: Coculture Of Fibroblasts and Osteoblastsmentioning
confidence: 99%
“…Previous approaches used dual step procedures where implants pre-coated with calcium phosphate were immersed in a medium containing dissolved bisphosphonate. Such procedures lack control over drug quantity and the amounts of loaded bisphosphonate (via adsorption to the outer layer of the coating) are limited [21]. The advantage that was obtained with nHA ALE in combination with ESD is the strong control over the quantity of bisphosphonate loading.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent these disadvantages of conventional bisphosphonate-based treatment, a therapy based on local (rather than systemic) effects of bisphosphonates is particularly appealing. Additionally, local treatment is capable of reducing the amount of drug used, which has been demonstrated for bisphosphonates by showing reduced osteoclastic activity even at low doses upon local delivery [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we have described an easy and inexpensive 64 method to obtain agarose/hydroxyapatite scaffolds with hierar-65 chical porosity at room temperature for bone repair application 66 Román et al, 2011). Biocompatibility studies 67 demonstrate that these scaffolds allow the culture of osteoblasts 68 inside and outside the material (Alcaide et al, 2010;Cabañas et al, 69 2014 (Cattalini et al, 2012;83 Coleman et al, 2011;Giger et al, 2013;Nancollas et al, 2006; 84 Rosenqvist et al, 2014). On the other hand, ibuprofen is commonly 85 prescribed to relieve pain due to inflammation that arises from 86 different osseous pathologies or surgical treatments (Mouriño and 87 Boccaccini, 2010;Rainsford, 2013), and it is also commonly 88 prescribed simultaneously with bisphosphonates in order to 89 minimize one of its main side effects: the "flu-like syndrome" 90 (Coleman et al, 2011 (Fig.…”
mentioning
confidence: 99%